Assessment and diagnosis of right ventricular failure—retrospection and future directions - Ro, Sun Kyun; Sato, Kei; Ijuin, Shinichi; Sela, Declan; Fior, Gabriele; Heinsar, Silver; Kim, Ji Young; Chan, Jonathan; Nonaka, Hideaki; Lin, Aaron C. W.; Bassi, Gianluigi Li; Platts, David G.; et al. (Frontiers in Cardiovascular Medicine, 2023)
The right ventricle (RV) has a critical role in hemodynamics and right ventricular failure (RVF) often leads to poor clinical outcome. Despite the clinical importance of RVF, its definition and recognition currently rely on patients’ symptoms and signs, rather than on objective parameters from quantifying RV dimensions and function. A key challenge is the geometrical complexity of the RV, which often makes it difficult to assess RV function accurately. There are several assessment modalities currently utilized in the clinical settings. Each diagnostic investigation has both advantages and limitations according to its characteristics. The purpose of this review is to reflect on the current diagnostic tools, consider the potential technological advancements and propose how to improve the assessment of right ventricular failure. Advanced technique such as automatic evaluation with artificial intelligence and 3-dimensional assessment for the complex RV structure has a potential to improve RV assessment by increasing accuracy and reproducibility of the measurements. Further, noninvasive assessments for RV-pulmonary artery coupling and right and left ventricular interaction are also warranted to overcome the load-related limitations for the accurate evaluation of RV contractile function. Future studies to cross-validate the advanced technologies in various populations are required.